Utilization Of Digital Media In IPS Learning (Case Study At SMP Negeri 3 Manokwari) - Welly Ervina Solissa; Sahrah Fadillah; Nurul Aulia; Sirajuuddin Saleh (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The use of digital media in Social Studies (IPS) learning is one of the important transformations in the world of education in the 21st century. This study aims to describe the actual conditions of digital media utilization in the Social Studies learning process at SMP Negeri 3 Manokwari, identify obstacles faced by teachers and students, and formulate relevant development strategies. The study used a descriptive qualitative approach with a case study method. Data collection was conducted through classroom observations, in-depth interviews with Social Studies teachers, the principal, and students, and analysis of lesson planning documents. The results show that some Social Studies teachers at SMP Negeri 3 Manokwari have utilized digital media in the form of learning videos, PowerPoint presentations, and the Google Classroom platform, but the intensity of use is still not optimal due to limited internet infrastructure, lack of teacher training, and low ownership of digital devices by students from low economic backgrounds. These findings emphasize the importance of school policy support, ongoing training for teachers, and the provision of adequate digital infrastructure to improve the quality of digital-based Social Studies learning in the West Papua region.